Do responsible employers attract responsible employees? - Karine Nyborg (IZA World of Labor, 2014)
Survey and register data indicate that many employees prefer a socially responsible employer and will accept a lower wage to achieve this. Laboratory experiments support the hypothesis that socially responsible groups are more productive than others, partly because they attract cooperative types, partly because initial cooperation is reinforced by group dynamics. Overall, the findings indicate corporate social responsibility may have cost advantages for firms.
Keywords: D22; D64; H41; Q52; 330; corporate social responsibility (CSR); employee motivation; productivity; wages